Molecular assemblies based on Cp*BiX2 units (X = Cl, Br, I): an experimental and computational study - Monakhov, Kirill; Zessin, Thomas; Linti, Gerald W. (Organometallics, 2011)
A series of pentamethylcyclopentadienyl-substituted bismuth halo complexes were prepared by the reactions of bismuth(III) halides BiX3 (X = Cl, Br, I) with LiCp* (Cp* = C5Me5) in 1:1 ratio. The crystal structures of [Cp*5Bi6Cl12][(thf)2Bi2Cl7] (1), [Cp*BiBr2]∞ (2), [{Cp*5Bi5Br9}{BiBr4}]2 (3), and [Cp*BiI2]∞ (4) were determined by single-crystal X-ray diffraction analysis. 1-4 display different types of aggregation, polymeric association, and Cp*-BiX2 bond hapticity depending on the halogen atom at Bi. The cationic portion of 1 is a distorted octahedral Bi6 cage that shows no Bi-Bi bonding, is capped by halo ligands and Cp* rings in a η5-fashion, and contains an interstitial Cl atom. The main structural difference in the bismuth halide framework between cationic portions {Cp*5Bi5Br9}+ in 3 and [Cp*5Bi6Cl12]+ in 1 is a neutral BiX3 unit complexed to the [{Cp*5Bi5Cl9}]+ fragment of the latter. 2 and 4 are zigzag polymers with different types of intermolecular interaction in the crystals. More ionic Cp*-Bi bonding results in higher hapticity and appears to favor cage formation, while more covalent bonding favors lower hapticity. According to quantum chemical calculations on the simplified gas phase models Cp*BiX2 (X = F, Cl, Br, I), the Cp* ring is attached via a η1(π)-bonding mode. The structural diversity of the observed assemblies is driven by the nature of Cp*-Bi bonding, which was examined by NBO analysis.